1983
DOI: 10.1056/nejm198309153091103
|View full text |Cite
|
Sign up to set email alerts
|

Association of an Inversion of Chromosome 16 with Abnormal Marrow Eosinophils in Acute Myelomonocytic Leukemia

Abstract: We identified 18 patients with an inversion of chromosome 16, inv(16)(p13q22), among 308 patients with newly diagnosed acute nonlymphocytic leukemia. Each of these 18 patients had acute myelomonocytic leukemia (M4 subtype) and eosinophils with distinctly abnormal morphology, cytochemical staining, and ultrastructure. These eosinophils constituted from 1 to 33 per cent of the nucleated marrow cells. In our series, every patient with acute myelomonocytic leukemia and abnormal eosinophils also had an abnormal chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
1
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(166 citation statements)
references
References 30 publications
7
156
1
2
Order By: Relevance
“…The pericentric inversion inv(16) (p13q22) is one of the most frequently occurring chromosomal rearrangements detected in the neoplasm, which has been reported to account for approximately 16% of all AMLs. 48,[52][53][54] The breakpoint involved in the inv(16) has recently been cloned and shown to involve the core binding factor b-gene (CBFb) on chromosome 16q22 and the smooth muscle heavy chain (MYH11) on 16p13. The formation of the chimeric CBFb/MYH11 fusion gene results in the disruption of the normal interaction of the transcription factor complex a, b and ETS.…”
Section: Cbfb/myh11 Fusion Transcript Analysismentioning
confidence: 99%
“…The pericentric inversion inv(16) (p13q22) is one of the most frequently occurring chromosomal rearrangements detected in the neoplasm, which has been reported to account for approximately 16% of all AMLs. 48,[52][53][54] The breakpoint involved in the inv(16) has recently been cloned and shown to involve the core binding factor b-gene (CBFb) on chromosome 16q22 and the smooth muscle heavy chain (MYH11) on 16p13. The formation of the chimeric CBFb/MYH11 fusion gene results in the disruption of the normal interaction of the transcription factor complex a, b and ETS.…”
Section: Cbfb/myh11 Fusion Transcript Analysismentioning
confidence: 99%
“…Patients with CBFb-AML account for about 5-8% of adults with de novo AML and they are frequently associated with specific characteristics. This AML subset is morphologically associated with the French-American-British (FAB) M4 subtype with an abnormal eosinophil component (M4eo) and extramedullary involvement may be present [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that peripheral blood stem collections contain Hodgkin's cells. 3 Here we show the use of selected stem cells (CD34 + ) for autografting after high-dose chemotherapy.…”
Section: G Martinellimentioning
confidence: 99%
“…[2][3][4] The molecular marker is detectable by reverse transcription-polymerase chain reaction assay (RT-PCR) [5][6][7][8][9] on RNA at the time of diagnosis, and could be particularly useful for monitoring MRD in patients who achieve complete clinical remission (CCR) after induction therapy. [10][11][12][13] Marcucci et al 14 and several other authors [10][11][12][13] have reported favorable clinical outcomes despite persistence of CBF␤/MYH11 transcripts detected by RT-PCR; similar findings have been reported for another core-binding-factor altered in AML, 15,16 in which positive expression of AML1-ETO transcript can persist after induction and consolidation chemotherapy without evidence of hematological relapse.…”
Section: Molecular Remission In Pcr-positive Acute Myeloid Leukemia Pmentioning
confidence: 99%